A survey of noise and hearing patterns in an Indian industry in Mysore city - P, Mahananda (Journal of All India Institute of Speech and Hearing)
Pollution has caused so much concern here and abroad that it is becoming a public nuisance. Among various pollutions, noise pollution has attracted a great deal of attention. As nation develops, as new industries are born, as consumer and transportation facilities increase, noise inevitably also spreads to more and more people. Rightly therefore more concern is being paid to the increasing occurrence of noise and its effects upon man